Cost-effectiveness of zinc supplementation for prevention of childhood diarrhoea in Tanzania. Issue 7 (11th July 2022) - Saronga, Happiness Pius; Manji, Karim; Liu, Enju; Duggan, Christopher P; Menzies, Nicolas A
Abstract: Objective: To assess the cost-effectiveness of prophylactic Zn supplementation for preventing diarrhoea in young children in Tanzania. Design: Cost-effectiveness analysis using decision-analytic modelling. Cost-effectiveness ratios were calculated as the incremental cost (2019 USD) per disability-adjusted life year (DALY) averted, from a societal perspective, and with a 3 % discount rate applied to future outcomes. Sensitivity analyses were performed to test the robustness of results to alternative assumptions. Setting: Tanzania. Participants: A hypothetical cohort of 10 000 children aged 6 weeks to 18 months. Results: The intervention costs of Zn supplementation were estimated as 109 800 (95 % uncertainty interval: 61 716, 171 507). Zn supplementation was estimated to avert 2200 (776, 3737) diarrhoeal episodes, 14 080 (4692, 25 839) sick days, 1584 (522, 2927) outpatient visits, 561 (160–1189) inpatient bed days, 0·51 (0·15, 1·03) deaths and 19·3 (6·1, 37·5) DALY (discounted at 3 % per year). Zn supplementation reduced diarrhoea care costs by 12, 887 (4089, 25 058). The incremental cost per DALY averted was 4950 (1678, 17 933). Incremental cost-effectiveness ratios (ICER) estimated from a health system perspective were similar to the results from the societal perspective. ICER were substantially lower (more favourable) when future outcomes were not discounted, but all ICER were above contemporary thresholds for cost-effectiveness in this setting. Conclusion: Prophylactic Zn reduced diarrhoea incidence and associated healthcare utilisation; however, it did not appear to be cost-effective for prevention of childhood diarrhoea in the scenario examined in this study. Reducing intervention costs, or identifying high risk groups for intervention targeting, may be needed to improve cost-effectiveness in this setting.